Klinefelter Syndrome with Poor Risk Extragonadal Germ Cell Tumor - Jeremy A. Konheim; Jonathan A. Israel; Scott E. Delacroix (Urology Case Reports, 2017)
Germ cell tumors are the most common malignancy in men aged 15-35 years old, with a small percentage presenting in an extragonadal location. These tumors are seldom identified in the gastrointestinal tract. There is increased risk of extragonadal germ cell tumors (EGCT) in men with Klinefelter syndrome (KS). We report a rare case of a 37-year-old male with KS and EGCT discovered in the duodenum and pelvis. After treatment with Bleomycin-Etoposide-Cisplatin (BEP), he developed growing teratoma syndrome (GTS) and myelodysplasia. Despite surgical excision of the pelvic growing teratoma, he unfortunately died secondary to complications of severe bone marrow suppression.